Visual field improvement after endoscopic transsphenoidal surgery in patients with pituitary adenoma - Ji, Xiaoyu; Zhuang, Xinyu; Yang, Siyuan; Zhang, Kai; Li, Xiaozhe; Yuan, Kun; Zhang, Xiaofeng; Sun, Xuebo (Frontiers in Oncology, 2023)
Purpose: To analyze and predict the possibility of visual field (VF) recovery after endoscopic transsphenoidal surgery (ETSS) in patients with pituitary adenoma, we investigated the factors affecting to improvement of visual field defect (VFD) and built a nomogram predictive model based on these risk factors, and studied further for specific recovery regions of VF associated with the improvement of VFD. Methods: The clinical data of patients who underwent ETSS for pituitary adenomas at a single center between the January 2021 and April 2022 were retrospectively analyzed. Univariate and multivariate analyses were used to determine the predictive factors affecting the improvement in the VF defect and specific recovery regions in patients with pituitary adenomas after ETSS. Results: We enrolled 28 patients who were hospitalized at our institution. Four clinical features, including compression of the optic chiasm, preoperative mean defect (MD), diffuse defect, and duration of the visual symptom, were chosen from the least absolute shrinkage and selection operator regression analysis and further stepwise method to establish the predictive nomogram. The nomogram’s area under the curve (AUC) was 0.912, indicating that the nomogram had a good degree of differentiation. A calibration plot was used to evaluate the predictive model’s calibration, and a decision curve was used to evaluate its clinical application value. The VF defects were improved in the 270–300° range (270–300: RR = 361.00, 95% CI: 21.01–6202.41). Conclusion: We developed a predictive nomogram model based on significant visual field improvement-associated factors after ETSS in patients with pituitary adenoma. Postoperative visual field improvement is likely to begin at 270–300° in the inferior temporal quadrant. This improvement would enable personalized counseling for individual patients by precisely predicting the visual field recovery after surgery.